2018
DOI: 10.3389/fpls.2018.00795
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Management of Rhizomania Disease—Insight Into the Changes of the Beet necrotic yellow vein virus RNA-3 Observed Under Resistant and Non-resistant Sugar Beet Fields

Abstract: Rhizomania disease, caused by the Beet necrotic yellow vein virus (BNYVV), is considered as one of the major constraints for sugar beet production, worldwide. As a result of the introgression of major resistance genes (Holly, Rz2) in commercially available sugar beet varieties, the virus has endured strong selection pressure since the 90s'. Understanding the virus response and diversity to sugar beet resistance is a key factor for a sustainable management of only few resistance genes. Here we report rhizomania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 56 publications
(88 reference statements)
1
30
0
Order By: Relevance
“…Interestingly, Koenig et al (2009b) found in field root samples of Rz1 resistant plants from the Pithiviers area genome reassortments consisting of either A-/P-type or B-/P-type. More recently, Galein et al (2018) confirmed this observation in the same area and could even identify plants containing A-, B-, and P-type. Both studies indicate genome reassortments between different BNYVV types, but it remains to be shown whether the presence of P-type RNA5 mediates Rz1 resistance-breaking in the background of A-or B-type.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Interestingly, Koenig et al (2009b) found in field root samples of Rz1 resistant plants from the Pithiviers area genome reassortments consisting of either A-/P-type or B-/P-type. More recently, Galein et al (2018) confirmed this observation in the same area and could even identify plants containing A-, B-, and P-type. Both studies indicate genome reassortments between different BNYVV types, but it remains to be shown whether the presence of P-type RNA5 mediates Rz1 resistance-breaking in the background of A-or B-type.…”
Section: Introductionsupporting
confidence: 59%
“…Furthermore, the variability in absorbance values between AYPR, VCHG, and VLHG suggests that the tetrad variants are associated with a different fitness advantage in the resistant genotype. This might be an explanation for the large variability of different tetrad variants found in natural virus populations (Galein et al, 2018;Weiland et al, 2019), which is also indicative for an ongoing virus evolution. The replacement of the RNA3 in the non-resistance-breaking BNYVV clone by an RNA3 derived from a resistance-breaking virus population demonstrated that two A-type populations can exchange genome components leading to infectious reassortments overcoming Rz1 resistance.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Chiba et al (2011) found that many isolates of the Italy A-III strain were able to overcome Rz1 resistance with various degrees of RB, whereas other virus strains (such as Germany [= B type], A-I, and A-II type strains) could not overcome Rz1-mediated resistance. Furthermore, RNA5-containing BNYVV (P-type strain) has been shown to have the ability to overcome Rz1 resistance (Pferdmenges et al, 2009;Bornemann and Varrelmann, 2011;Chiba et al, 2011;Galein et al, 2018). However, the pathogenic role of RNA5 in RB virus incidence, as well as non-RB virus incidence, remains unclear.…”
Section: Beet Necrotic Yellow Vein Virus Is the Type Member Of The Genusmentioning
confidence: 99%